OXIDATIVE STRESS AND OBSTETRIC COMPLICATIONS IN PREGNANT WOMEN WITH INHERITED THROMBOPHILIA WITH AND WITHOUT LOW MOLECULAR WEIGHT HEPARIN THERAPY - Maglic, Dragana; Mandic Markovic, Vesna; Bogdanovic Pristov, Jelena; Maglic, Rastko; Dzatic Smiljkovic, Olivera; Anicic, Radomir; Mandic, Milica; Mitrovic, Jelena; Skrijelj, Sabrina (Medical Research, 2024)
ABSTRACT:Introduction: Inherited thrombophilia (IT) presents genetic conditions associated with risk of deep vascular thrombosis (DVT) and obstetric complications (OC) such as preeclampsia (PE), fetal growth restriction (FGR), stillbirth and placental abruption (PA). The aim of our study was to evaluate frequency of OC and oxidative stress (OS) in women with IT during pregnancies with and without low molecular weight therapy (LMWH), comparing with women with healthy pregnancies.Materials and methods: We evaluated 60 pregnant women with IT diagnosed before ongoing pregnancy based on previous DVT or OC (study group) and 60 healthy pregnant women (control group). In all subject’s blood samples before delivery and placental tissue were collected and activity of CAT, GPX, GH, SH,  GR, CuZnSOD, and MnSOD were determined. Results After the introduction of LMWH therapy, the total number of OC decreased significantly in women with IT. Analyzing the association between OC and different kinds of IT, we found significant association only between Factor V Leiden mutation and Protein C deficiency with GH/PE. Levels of SH is higher in IT; CAT, GPH and GR are three times more active in patients with IT with LMWH therapy compared to control group. Conclusion Values ​​of OS parameters in pregnant women with IT during delivery may confirm increased OS in those patients indicating that introduction of antioxidant therapy may be advisable.
Keywords: Thrombophilia, Obstetric complication, Oxidative stress